Optimization of media for in vitro propagation and rooting of creole grapevine varieties utilized for pisco making - González, Eugenio (2011)
The protocols and culture media available for in vitro propagation and rooting of grapevine have not yet been adjusted to the creole varieties used for pisco making. In this paper we explored the use of culture media for the propagation of varieties Quebranta, Negra Criolla, Albilla, Italia and Torontel and for rooting varieties of Quebranta, Albilla and Torontel based on known standard culture media.To address this issue, 11 media derived from the standard propagation medium for grapevine (1X Murashige & Skoog medium, 3% sucrose, 1 mg/L benzilaminopurine, and 0,8% agar) with diminished medium strength and/or hormone concentration were tested. In addition, 5 concentrations of naphtalen acetic acid or indol acetic acid were tested for rooting. We found that Quebranta, Albilla, and Italia varieties show a better growth in the standard propagation medium; by contrast, Negra Criolla and Torontel grew better in media with diminished benzilaminopurine concentrations (0,25 and 0,5 mg/L, respectively). Quebranta rooted better with 80 μg/L naphtalen acetic acid or 2 mg/L indol acetic acid, while Albilla and Torontel showed better rooting results with 2 and 1 mg/L indol acetic acid, respectively.